2021
DOI: 10.1038/s41598-021-84217-6
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of labile organic carbon, enzyme activities and microbial communities of two forest soils across seasons

Abstract: Soil labile organic carbon (LOC) responds rapidly to environmental changes and plays an important role in carbon cycle. In this study, the seasonal fluctuations in LOC, the activities of carbon-cycle related enzymes, and the bacterial and fungal communities were analyzed for soils collected from two forests, namely Betula albosinensis (Ba) and Picea asperata Mast. (Pa), in the Qinling Mountains of China. Results revealed that the seasonal average contents of microbial biomass carbon (MBC), easily oxidized orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
2
19
1
Order By: Relevance
“…Additionally, soil enzymes, produced by soil microorganisms, are reported to regulate the overall processing of SOC through degrading different molecules [13] or depolymerizing macromolecular substrates [14]. Some enzymes (e.g., β-Glucosidase and β-Xylosidase activities) show a strong relationship with SOC content and are generally reported to be good indicators of soil biological change [15,16]. It is remarkable that, even if the complexity of SOC-related mechanisms is widely recognized, most studies focused on a single factor, with fewer focused on multiple factors regulating SOC.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, soil enzymes, produced by soil microorganisms, are reported to regulate the overall processing of SOC through degrading different molecules [13] or depolymerizing macromolecular substrates [14]. Some enzymes (e.g., β-Glucosidase and β-Xylosidase activities) show a strong relationship with SOC content and are generally reported to be good indicators of soil biological change [15,16]. It is remarkable that, even if the complexity of SOC-related mechanisms is widely recognized, most studies focused on a single factor, with fewer focused on multiple factors regulating SOC.…”
Section: Introductionmentioning
confidence: 99%
“…As the basic unit of soil, aggregate plays a key role in C cycling [17]. Containing more than 90% of sequestered SOC, aggregate can be divided into macro-(>0.25 mm) and micro-(<0.25 mm) aggregates [15,16]. Previous studies have shown that macroaggregate (>0.25 mm) contains more SOC content than micro-aggregate (0.053-0.25 mm), the same as labile SOC [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations